IMPROVING STUDENT LEARNING MOTIVATION THROUGH LEARNING ASSISTANCE ACTIVITIES - Uswatun Solikhah; Muhammd Sholikhun; Laili Syarifah (khidmatan, 2022)
Student learning assistance at home is very much needed by a student, this is important to do considering the limitations of teachers at school in teaching students in the classroom. Tutoring is an effort made to provide assistance to students to better understand the material. If a student already understands, it will affect the enthusiasm and motivation of student learning from now on to the future. The purpose of this study is to foster student learning motivation through the level of student understanding of a material that is implemented through tutoring activities. the method in this study using the PAR (Participation Action Research) method. Participatory Action Research (PAR) is a research method that is carried out in a participatory manner among community members, namely Santri at TPQ Nurudholam Dusun Sawangan. The results of the implementation of this tutoring program were able to foster students' enthusiasm for learning, which was proven enthusiastically during learning mentoring activities.